Harvard business review on managing people (Harvard Business School P. BostonUS, 1999)
Identifies and discusses four types of business community, namely: networked, mercenary, fragmented, and communal. Examines the relationship between a manager's expectation and an employee's performance. Discusses topics including: six myths about pay; conflicting issues in empowerment; managing different identity groups effectively; and, advantages and disadvantages of the alternative workplace option. Examines the set-up-to-fail syndrome, showing how bosses and employees contribute to it, and how it can be reversed.
Located in the Learning Resource Centre